Pengaruh Budya Korea Terhadap Identitas Gen Z: Antara Lintas Budaya dan Krisis Jati Diri - Rusdi, Widya Anugrah; Najamuddin, Najamuddin; Alwi, Alimin (Metta : Jurnal Ilmu Multidisiplin, 2025)
The explosive rise of the Korean Wave has not only transformed Gen Z’s entertainment preferences but has also penetrated the most personal domain: the way they understand, evaluate, and construct their sense of identity. This study aims to analyze how Korean culture (the Korean Wave) influences the identity formation of Generation Z in Indonesia and to identify potential identity crises emerging from this cross-cultural process. Using a qualitative method through in-depth interviews, observation, and digital document analysis, this research involves informants aged 15–25 who have high exposure to Korean culture. The findings show that Korean culture positively contributes to Gen Z identity through enhanced creativity, self-expression, work ethic, and the formation of fandom-based social communities. However, the study also reveals negative impacts, including pressure from beauty standards, tendencies toward consumerism, excessive social comparison, and a weakening attachment to local culture, which may trigger identity confusion. This study highlights that Gen Z identity is formed through a negotiation between local and global values and that cultural literacy is a key factor in preventing identity crises. The study contributes academically by expanding understanding of the dynamics of youth identity in the context of cultural globalization and offering new perspectives on the role of popular culture in identity construction.